The development of professional military education at the United States Air Force Academy - Kennedy, Douglas Blake (Kansas State University, 2017)
This dissertation examines the development of the professional military studies curriculum at the United States Air Force Academy. The study explores the rationale behind establishing an Air Force Academy, along the lines similar to the U.S. Military Academy at West Point or the U.S. Naval Academy at Annapolis. The quest for an additional academy emphasized the need for specialized training of air force cadets and creating a common bond for its future officer corps, rather than recognizing the necessity to equip them with a professional military education regarding warfare and how air power influences war, for example. This trend continued in the two main studies used to justify the Air Force Academy, as well as the development of the initial curriculum, where an integrated academic curriculum, one that emphasized both the sciences and engineering as well as the social sciences and humanities, placed any discussion of professional military studies on the back burner. The challenge of the Academy’s general academic curriculum on the cadet’s time left little room for the development of a strong, rigorous professional military studies program. However, the confluence of a cheating scandal at West Point and the resulting report, as well as a reflection during the 25th anniversary of the Academy’s founding in 1979, which developed questions on the professional military studies program within the curriculum, led to the establishment of a Permanent Professor within the Deputy Commandant for Military Instruction, and resulted in drastic changes to the curriculum for the cadets, specifically involving professional military studies. Today, the United States Air Force Academy has a Department of Military and Strategic Studies under the overall authority of the Dean of Faculty. This department has as its charter the role to provide “the study of the context, theory, and application of military power”—with special emphasis on the role of airpower to the art and science of war. The document that helps define the duty of the department also states that this necessary study for officer candidates constitutes “the essence of a military academy education” and, most certainly, the central core of a professional military studies program.
Keywords: Military profession; Military education; United States Air Force Academy; Professional military studies; Professional military education; Officer development